(untitled) (Research, Society and Development, 2022)
This study identified the marketing strategies in social media used by retail meat stores in the municipality of Porto Alegre, Southern Brazil. Data was collected through posts available on social media and on websites of 18 stores in November 2018, each social media was analyzed on the same day to avoid bias of new followers or posts. In this analysis, 38 descriptor variables were identified, coded, and grouped by Cluster Analysis. The variables were compared in a one-way PERMANOVA with Bonferroni correction. To our knowledge, none other research analyzes the virtual strategies of this traditional sector and offers pointers for beef stores to survive on social media. To understand this adaptation is even more relevant considering the reality of Covid-19 pandemic, and we highly suggest future studies to analyze this scenario to understand the changes in marketing and in consumer’s responses. The analysis of clusters identified three types of meat stores: traditional; dynamic and UpToDate; and a group with diffuse strategies, with different marketing strategies on social media. The most advertised variables were associated with product characteristics, such as quality, sensorial aspects, and beef cut. On the other hand, intangible aspects such as environmental concerns, certifications, where barely mentioned.